2007
DOI: 10.1299/jee.2.708
|View full text |Cite
|
Sign up to set email alerts
|

Solar Rankine Cycle System Using Scroll Expander

Abstract: A unique solar thermal electric system is proposed and tested in the present study. In this system, an organic working fluid, which is suitable for a temperature range appropriate for solar energy, is adopted. We call this system as "solar organic Rankine cycle system" (SORCS). In order to improve the thermal efficiency by using solar energy, a displacement-type scroll expander and compound parabolic concentrator (CPC) solar collector are used. This system consists of very simple components that are similar to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
34
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 92 publications
(35 citation statements)
references
References 4 publications
0
34
0
1
Order By: Relevance
“…It is found that the presence of hydrogen bond in certain molecules such as water, ammonia and ethanol may result in lager vaporizing enthalpy, and is regarded as inappropriate for ORC system. Experimental study was also proposed to improve the thermal efficiency by using solar energy [7]. A displacementtype scroll expander and compound parabolic concentrator solar collector are used.…”
Section: Introductionmentioning
confidence: 99%
“…It is found that the presence of hydrogen bond in certain molecules such as water, ammonia and ethanol may result in lager vaporizing enthalpy, and is regarded as inappropriate for ORC system. Experimental study was also proposed to improve the thermal efficiency by using solar energy [7]. A displacementtype scroll expander and compound parabolic concentrator solar collector are used.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, there ought to be included transmission losses, which permit to say that the micro CHP units, planned to be developed in the near future, are quite promising technologies. Literature sees several studies where different micro-ORC systems designed for heat production and electricity generation were studied, see for example Nguyen et al [1], Saitoh et al [2], Lemort et al [3]. There are still issues requiring particular attention in appropriate implementation of that technology in practice, namely the expansion device, which in the above cases was a modified scroll compressor to the expansion mode.…”
Section: Introductionmentioning
confidence: 99%
“…To design a displacement-type expander with a variable expansion mechanism, the required optimal expansion profile of the working fluid must first be known; the expansion profile should fit the cell volume profile from the inlet (intake port) to the outlet (discharge port) of the displacement-type expander. Screw and scroll expanders [8] [12] are two types of displacement-type expanders that are often employed in low-temperature Rankine cycle systems. In this study, we first analyzed the expansion profiles of three typical working fluids: HFC245fa (dry fluid), ammonia (wet fluid), and supercritical CO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…The evaporator and condenser are heat exchangers in the cycle that absorb and release heat. [8] . The cycle starts by the pump pushing the working fluid to the evaporator.…”
Section: Introductionmentioning
confidence: 99%